Evaluation of the Ages and Stages Questionnaire (ASQ 3) as a developmental screener at 9, 18, and 24 months. (August 2020) - Agarwal, Pratibha Keshav; Xie, Huichao; Sathyapalan Rema, Anu Sathyan; Rajadurai, Victor Samuel; Lim, Sok Bee; Meaney, Michael; Daniel, Lourdes Mary
Abstract: Background: Without the use of standardized screening tools, only 30% of the estimated 5–15% of children with developmental delay can be identified, potentially delaying intervention. Aim: 1) To evaluate the ASQ-3's reliability and validity at 9, 18, and 24 months and to compare the results with normative USA data. 2) To determine the risk factors for a screen positive result, which requires further evaluation. Methods: Study of 649 low-risk children was part of a larger longitudinal cohort study, the GUSTO project. Socio-demographic and ASQ3 data were analyzed to estimate reliability, validity, mean ASQ scores, and cut-off scores. Results: ASQ-3 showed an acceptable to good internal consistency (0.49–0.83) and a medium level of correlations (0.22–0.59) between the five domains but differed significantly compared to normative USA data. Using local cut-off scores, 12.6–13.6% of the cohort had a positive screen in ≥ 1 domain at 9, 18, or 24 months. ASQ-3 screening categorization was consistent, with only 3–11% of children showing change in categorization longitudinally. On regression, lower family income (OR 3.3–9.42) and maternal education (OR2.65–3.03) were predictive of a positive screen across domains and age intervals. Interpretation: ASQ-3 is a useful, valid screening tool in Singapore. Further research is needed to investigate item functioning and to assess its concurrent validity with a criterion standard tool for culturally sensitive developmental screening. Highlights: Reliability of the ASQ-3 in a multi-ethnic population The importance of developing local normative data for developmental screening The psychometric adequacy of the ASQ-3 in the Singapore context The need for targeted screening in high risk families The important association of environmental risk factors with developmental delay